Simulasi Monte Carlo dalam Prediksi Jumlah Penumpang Angkutan Massal Bus Rapid Transit Kota Padang - Khaliq Alfikrizal (SAFE-Network, 2021)
Bus Rapid Transit is a system of bus facilities, services and comfort which is used to increase speed and reliability and is integrated with a strong transit identity through high quality services. Trans Padang is a land transportation based on Bus Rapid Transit in Padang City which is managed by the Transportation Agency which started operating in January 2014 with a total bus fleet of 10 units on the Lubuk Buaya-Pasar Raya Padang route. Currently it has 2 corridors operating out of 6 corridors designed. This study aims to predict the number of Bus Rapid Transit passengers in Padang City and determine the level of accuracy of simulation data with real data using the Monte Carlo method. The data used to predict the number of passengers is data on the number of passengers from January 2017 to December 2019. From the simulations carried out, simulated accuracy is obtained for predicting the number of passengers with an average accuracy of above 80%. Based on a fairly high level of accuracy, the application of the Monte Carlo method to predict the number of Bus Rapid Transit passengers in Padang City is considered to be able to predict the number of passengers in the following year.